Ghrelin in Female and Male Reproduction. (14th March 2010) - Dupont, Joëlle; Maillard, Virginie; Coyral-Castel, Stéphanie; Ramé, Christelle; Froment, Pascal
Abstract : Ghrelin and one of its functional receptors, GHS-R1a (Growth Hormone Secretagogue Receptor 1a), were firstly studied about 15 years. Ghrelin is a multifunctional peptide hormone that affects several biological functions including food intake, glucose release, cell proliferation … Ghrelin and GHS-R1a are expressed in key cells of both male and female reproductive organs in several species including fishes, birds, and mammals suggesting a well-conserved signal through the evolution and a role in the control of fertility. Ghrelin could be a component of the complex series of nutrient sensors such as adipokines, and nuclear receptors, which regulate reproduction in function of the energy stores. The objective of this paper was to report the available information about the ghrelin system and its role at the level of the hypothalamic-pituitary-gonadal axis in both sexes.